ANALISIS KANDUNGAN LOGAM TIMBAL, KADMIUM DAN MERKURI DALAM PRODUK KRIM PEMUTIH WAJAH - Erasiska '; Subardi Bali; Tengku Abu Hanifah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Whitening cream is a mixture of chemicals or other materials which is able to whiten the skin. The presence of heavy metals such as Pb, Cd and Hg in the whitening cream products are very dangerous, because if the heavy metal ions adsorbed into organs, it will cause health problems. This study aims to determine the metal content of lead, cadmium and mercury in the whitening cream products. The sample of whitening cream which is used in this study consists of day cream and night cream. 6 samples ( 3 of daycream and 3 of night cream) were purchased randomly in Pekanbaru market to be analyzed by using atomic absorption spectrophotometer. The result of the study showed the highest contentof Pb was seen in the sample of day whitening cream with values of C134,91 μg/g and the highest content of Cd was seen in the sample of night whitening cream with values of C21,55 μg/g while the highest content of Hg was shown by the sample of night whitening cream with values of B24,18 μg/g. All the results are above the safe limit determined by the National Agency of Drug and Food Control of the Republic of Indonesia BPOM RI No. HK 03.1.23.08.11.07331 tahun 2011.